Numerical Modeling of Cooling Water Droplets using a Two-Way Coupling Approach - Franco, André Filipe Romão (2019)
The present dissertation focuses on the study of the process of cooling and freezing of free falling water droplets. The freezing phenomenon is of extreme relevance in aviation since the impact of drops on lifting surfaces of an aircraft and consequent accretion can lead to the occurrence of incidents and accidents. In order to prevent the formation and accretion of ice, there are several systems to combat this hazard. Critical areas of an aircraft are usually protected by these de-icing systems. However, although these methods can evaporate drops of water or melt the accreted ice, there is still the possibility of downstream ice formation due to new freezing of the ice-water mixture in unprotected areas. Thus, there is a need to study and adapt the existing physical and mathematical models for a better approximation to real-life situations, in order to contribute to a better understanding of this phenomenon and consequently lead to a reduction in the number of incidents and accidents, safety conditions. The objective of this work is to perform a numerical study with the purpose of studying the cooling of free falling water droplets for different diameters and humidity ratios. Ranz-Marshall relations are used, with and without a correction factor, in addition to the Abramzon and Sirignano approach to take into account the effects of convection. A Two-Way Coupling approach is used being the predictions compared with experimental data and numerical predictions in a One-Way Coupling approach.